2017
DOI: 10.1080/19336934.2017.1396399
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the nicotinic acetylcholine receptor subunit gene Dα1 confers insecticide resistance, but at what cost?

Abstract: Nicotinic acetylcholine receptors (nAChRs) have vital functions in processes of neurotransmission that underpin key behaviors. These pentameric ligand-gated ion channels have been used as targets for insecticides that constitutively activate them, causing the death of insect pests. In examining a knockout of the Dα1 nAChR subunit gene, our study linked this one subunit with multiple traits. We were able to confirm previous work that had identified Dα1 as a target of the neonicotinoid class of insecticides. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…We found that the effect on the biological traits tested was moderate, with Q68* (Ccα6 3aQ68*Δ3b-4 /Ccα6 3aQ68*Δ3b-4 ) and Q68*-K352* (Ccα6 3aQ68*-K352* /Ccα6 3aQ68*-K352* ) isolines showing longer developmental time but higher male weight than C strain, whereas females of both resistant isolines and susceptible C strain did not differ in weight. However, mutations that would lead to a loss-of-function phenotype may affect behavioral patterns, as it has been reported for a Dα1 knockout mutant with a significant fitness cost in terms of severe mating behavior defects and an altered sleep phenotype (Somers et al 2017). Thus, we explored the possibility that behavioral fitness traits (parapheromone detection by wind tunnel and electrophysiological antennal assays, and mating success) could be affected in males of the Q68* and Q68*-K352* isolines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the effect on the biological traits tested was moderate, with Q68* (Ccα6 3aQ68*Δ3b-4 /Ccα6 3aQ68*Δ3b-4 ) and Q68*-K352* (Ccα6 3aQ68*-K352* /Ccα6 3aQ68*-K352* ) isolines showing longer developmental time but higher male weight than C strain, whereas females of both resistant isolines and susceptible C strain did not differ in weight. However, mutations that would lead to a loss-of-function phenotype may affect behavioral patterns, as it has been reported for a Dα1 knockout mutant with a significant fitness cost in terms of severe mating behavior defects and an altered sleep phenotype (Somers et al 2017). Thus, we explored the possibility that behavioral fitness traits (parapheromone detection by wind tunnel and electrophysiological antennal assays, and mating success) could be affected in males of the Q68* and Q68*-K352* isolines.…”
Section: Discussionmentioning
confidence: 99%
“…The need to investigate fitness, behavioral and life-history traits that require the function of receptors being targeted by insecticides has been highlighted (Perry and Batterham 2018). While nAChRs may have many roles in behavior, the known roles for the different subunits identified in D. melanogaster currently include sleep (Dα1, Dα3 and Dα4- Shi et al 2014;Somers et al 2017;Wu et al 2014), courtship (Dα1- Somers et al 2017) and escape response (Dα7- Fayyazuddin et al 2006). Only a few studies have considered how spinosad resistance affects behavior and the impact that loss-of-function or truncated α6 transcripts could have.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Genome editing with CRISPR/Cas9 or the use of model organisms such as D. melanogaster with the function of whole genes effectively removed may help to answer this question. Indeed, D. melanogaster with a knockout of the α1 nAChR gene was resistant to imidacloprid and nitenpyram [19]. Consistent with this, it was found that RNAi of α1 in Leptinotarsa decemlineata decreased sensitivity to imidacloprid and thiamethoxam [20].…”
Section: Nicotinic Acetylcholine Receptorsmentioning
confidence: 60%
“…We found that the effect on the biological traits tested was moderate, with Q68* (Ccα6 3aQ68*Δ3b-4 /Ccα6 3aQ68*Δ3b-4 ) and Q68*-K352* (Ccα6 3aQ68*-K352* /Ccα6 3aQ68*-K352* ) isolines showing longer developmental time but higher male weight than C strain, whereas females of both resistant isolines and susceptible C strain did not differ in weight. However, mutations that would lead to a loss-of-function phenotype may affect behavioral patterns, as it has been reported for a Dα1 knock-out mutant with a significant fitness cost in terms of severe mating behavior defects and an altered sleep phenotype (Somers et al, 2017a). Thus, we explored the possibility that behavioral fitness traits (parapheromone detection by wind tunnel and electrophysiological antennal assays, and mating success) could be affected in males of the Q68* and Q68*-K352* isolines.…”
Section: Discussionmentioning
confidence: 97%
“…Only a few studies have considered how spinosad resistance affects behavior and the impact that loss of function or truncated α6 transcripts could have, despite nAChRs may have many roles in behavior (Perry and Batterham, 2018). The known roles for the different subunits identified in D. melanogaster currently include sleep, Dα1, Dα3 and Dα4 (Shi et al, 2014;Wu et al, 2014;Somers et al, 2017a), courtship, Dα1 (Somers et al, 2017a) and escape response, Dα7 (Fayyazuddin et al, 2006). Changes to feeding behavior in Frankliniella occidentalis (Li et al, 2017) and reduced competitive mating in Heliothis virescens (Wyss et al, 2003) have been reported, but the molecular basis for spinosad resistance was unknown in both cases.…”
Section: Chapter 2 Functional Characterization and Fitness Cost Of Smentioning
confidence: 99%